2016
DOI: 10.1111/vde.12295
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TLR‐2 and TLR‐4 mRNA in feline polymorphonuclear neutrophils exposed to Microsporum canis

Abstract: The overexpression of TLR-2 and TLR-4 mRNAs in stimulated feline PMNs suggests that these receptors are involved in the host immune response through the recognition of M. canis PAMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Myeloid cells, keratinocytes and fibroblasts increase TLR-2 and TLR-4 mRNA expression upon interaction with dermatophytes (43,53). In vitro studies with feline neutrophils showed an increase in TLR-2 and TLR-4 mRNA levels after stimulation with live and heat-killed M. canis arthroconidia (54). Recently, Celestrino et al (55) reported that TLR-2 is important for T. rubrum conidia phagocytosis and proinflammatory cytokines production by human monocytes.…”
Section: Toll-like Receptorsmentioning
confidence: 98%
“…Myeloid cells, keratinocytes and fibroblasts increase TLR-2 and TLR-4 mRNA expression upon interaction with dermatophytes (43,53). In vitro studies with feline neutrophils showed an increase in TLR-2 and TLR-4 mRNA levels after stimulation with live and heat-killed M. canis arthroconidia (54). Recently, Celestrino et al (55) reported that TLR-2 is important for T. rubrum conidia phagocytosis and proinflammatory cytokines production by human monocytes.…”
Section: Toll-like Receptorsmentioning
confidence: 98%
“…In case of infection, keratinocytes are the cells initially encountered by dermatophytes. They can detect pathogens via pathogen-associated molecular pattern recognition, by using pattern recognition receptors: toll-like receptors (TLRs) 2, 4, and 6, notably (Brasch et al, 2014;Cambier et al, 2016;García-Madrid et al, 2011). Activation of pattern recognition receptors on keratinocytes induces signaling pathways, leading to expression and release of pro-inflammatory cytokines and AMP.…”
Section: Introductionmentioning
confidence: 99%
“…By analysis of PMN maintained in culture, the of IL-1β, IL-8, and TNFα and the production of neutrophil extracellular traps (NET) by this cell type were observed when PMN are incubated in the presence of T. benhamiae or M. canis [26,86]. Overexpression of TLR-2 and -4 mRNA was further characterized in PMN exposed to M. canis [87]. In addition, release of TNFα and IL-1β by macrophages challenged by T. rubrum was measured on a simple culture model [34,88].…”
Section: Recruitment Of the Immune System Through Activation Of Local...mentioning
confidence: 99%